Synthesis and characterization of silica coated magnetic nanoparticles - Drmota, Ana (Informacije MIDEM, 2011)
Magnetic (γ-Fe_2O_3) nanoparticles coated with silica (SiO_2) and a narrow particle size distribution were prepared in microemulsion system: water/(SDS+1-butanol)/cyclohexane. The influence of the concentration of reactants in aqueous phase, the temperature of reaction, the pH value during the precipitation of hydroxides and the type of surfactant, on the nature of γ-Fe_2O_3 nanoparticles were investigated. The thickness of SiO_2 shell was carefully controlled by the amount of tetraethoxysilane (TEOS) added to the microemulsion after the precipitation step. Prepared uncoated and coated γ-Fe_2O_3 nanoparticles were characterized using transmission electron microscopy (TEM), X-ray diffractometry (XRD) and specific surface area measurements (BET). The specific magnetization (DSM-10, magneto-susceptometer) of the prepared samples was also measured. The specific magnetization of the γ-Fe_2O_3 nanoparticles depended on their size, ranging from 14 to 49 Am^2/kg. The specific magnetization of coated γ-Fe_2O_3 nanoparticles sharply decreased due to the non-magnetic nature of SiO2 layer.
Keywords: magnetic nanoparticles; magnetni nanodelci; microemulsion method; mikroemulzijska metoda; nanotehnologija; silica; silicijev dioksid; silika; železov oksid